Properties of binder-bentonite-sand for construction of seepage cut-off walls - Tan, Yi Yin (Nanyang Technological University, 2023)
Sandy soils have engineering limitations such as high groundwater flow due to its porous continuum. As a result, seepage cut-off walls are required to be built to minimise the consequential adverse effects. The cut-off walls are often made with a mixture of binder, bentonite and in-situ sandy soil. Ordinary Portland cement (OPC) has been widely adopted for construction of seepage cut-off walls. However, the growing environmental awareness has urged to lower the carbon footprint caused by the use of OPC. Therefore, this study utilizes an alternative low-carbon binder of magnesia (MgO)-activated ground granulated blast-furnace slag (GGBS) to stabilise the soil mixtures in cut-off walls. This study is a part of a dual project and it focuses on inland application, whereas another study by Chao (2023) focuses on marine application. The effectiveness of MgO-GGBS was compared with other binder types such as OPC and quicklime (CaO)-activated GGBS. Different bentonite types, which included sodium, calcium and seawater-resistant bentonites, were used in this study. The properties of sand-bentonite-binder mixture, including bulk density, water content, unconfined compressive strength (UCS) and permeability, were evaluated. The results indicated that MgO-GGBS was a promising binder that performed better than OPC and CaO-GGBS. In particular, binder with MgO:GGBS ratio of 1:9 in combination with calcium bentonite produced the best performing sand-bentonite-binder mixture in terms of UCS, with permeability below the specified limit. This was due to the formation of mesh-like calcium silicate hydrate (C-S-H) during the hydration of MgO-GGBS, shown in scanning electron microscope (SEM), which bonded soil particles to form a well-compacted microstructure.